The Nengget Tradition of The Karo Ethnic: Semiotic Studies - Sitepu, Esti Putri (Institute of Computer Science (IOCS), 2020)
Every ethnicity has various types of traditions that differ from one another. This shows that there are many different types of traditions that exist in Indonesia, especially in North Sumatra. As with one of the Karo ethnic traditions, the nengget tradition. The nengget tradition is a ceremony carried out in families who have been married for a long time but have not yet had children. This ceremony can also be performed on families who already have children but are all female or male. The purpose of this research is to describe the form, function, meaning, and the value contained in the nengget tradition of ethnic Karo. The benefits of this research can provide input for writers in increasing knowledge about the nengget tradition of the Karo ethnicity,